Critical View of Safety in Laparoscopic Cholecystectomy: Can it prevent bile duct injuries. An Institutional Prospective Observational Study - Singh, Tejinder Paul; Kumar, Ashwani; Singh, Simrandeep; Singh, Jaswinder; Pasi, Dinesh Kumar; Dhamija, Parth; Saini, Anshu; Ojassvi Rishi (GMC Patiala Journal of Research and Medical Education, 2024)
Background Laparoscopic Cholecystectomy is the most commonly performed procedure and is the ‘gold standard’ for the treatment of cholelithiasis, however, it is associated with a preventable complication that is bile duct injury. Strasberg, in 1995 suggested a technique called “Critical View of Safety” (CVS) to avoid this complication. The effectiveness of CVS in preventing bile duct injuries is still debatable. Methods This prospective trial was conducted on 100 patients posted for Laparoscopic cholecystectomy in the Department of General Surgery, Government Medical College and Rajindra Hospital, Patiala during the study period of May 2019 to December 2020. An attempt was made to achieve critical view of safety in each case. All the patients were assessed for various patient related and surgery related parameters which might affect the outcome and the results were evaluated. Results Critical view of safety could not be achieved in 14% of patients, all these patients were overweight (BMI = 25 to 29.9) and had longer hospital stay. 12 % of the patients were converted to open cholecystectomy and 2% had bile duct injuries. Conclusion Critical view of safety is an effective method of preventing bile duct injuries and thereby minimizing complications while performing laparoscopic cholecystectomy. However further studies to strengthen these results may be warranted.